DISCOURSE ON MEDIA: Bringing Hot News into ELT's Classroom Discussion - Budi Hamuddin (Universitas Negeri Padang, 2015)
This paper presents a perspective in managing English language teaching (ELT) situation into more interesting in Discourse Analysis class. It aims to introduce and give a brief explanation on how to analyze the recent hot news or current issucs in the media using DA approach and bringing the students into a deeper Discussion on ELT sihration. Tbe. idea of analyzing a discourse of hot news and brought into ELT classroom, promising an advantageous and benefits for both students and lectures. For learners. Discourse Analysis uses to show and introduce how to examine news in the media in some levels; text. discursive practice. social practice and various ways qf analyzing media depends.on what sort of discourse being presented. Whereas for the lecturers, the idea of bringing hot nervs into ELT classroom, can be used as a strategy to empower the students more active in proposing or counter opinion in a forum of class discussion as well as teaching the class to be more aware and critical regarding to the news posted in the media.